The specificity of units with specialized meaning: polysemy as explanatory factor - Adelstein, Andreína; Cabré, María Teresa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In linguistics and terminology, few are the works that describe, in an integrated manner, terminological units and words. Neither are there models explicitly including, in their lexical representation, specialized meanings. We start from the hypothesis which states that the lexical unit (LU) is not per se either word or term, but a lexical form associated to all information relative to the different modules of the grammar in which it participates (Cabré 1999d, 2000). According to the communicational situation in which it is used, it either activates or not a specialized value. These values maintain a polysemic relationship with each other. The goals of this paper are to establish some elements that allow for an empirical foundation for the stated hypothesis on the LU, and to describe the kinds of features that compose semantic information and the configurations activated in specialized meanings.